The Use of Calcium Phosphate Bioceramics for the Treatment of Osteomyelitis - Cláudia Suellen Ferro Oliveira; Irina Negut; Bogdan Bita (Ceramics)
Bone infections, particularly osteomyelitis, present significant clinical challenges due to their resistance to treatment and risk of progressing to chronic disease. Conventional therapies, including systemic antibiotics and surgical debridement, often prove insufficient, especially in cases where biofilms form or infection sites are difficult to access. As an alternative, calcium phosphate bioceramics have emerged as a promising strategy for treating bone infections. These materials offer key advantages such as biocompatibility, osteoconductivity, and the ability to be engineered for controlled drug delivery. Calcium phosphate bioceramics can serve as scaffolds for bone regeneration while simultaneously delivering antibiotics locally, thus addressing the limitations of systemic therapies and reducing infection recurrence. This review provides an overview of osteomyelitis, including its pathogenesis and conventional treatment approaches, while exploring the diverse therapeutic possibilities presented by calcium phosphate bioceramics. Special attention is given to hydroxyapatite, tricalcium phosphate, and their composites, with a focus on their therapeutic potential in the treatment of bone infections. The discussion highlights their mechanisms of action, integration with antimicrobial agents, and clinical efficacy. The dual capacity of calcium phosphate bioceramics to promote both bone healing and infection management is critically evaluated, highlighting opportunities for future research to address current challenges and enhance their clinical application in orthopedics and dentistry. Future research directions should focus on developing calcium phosphate bioceramic composites with enhanced antibacterial properties, optimizing drug-loading capacities, and advancing minimally invasive delivery methods to improve clinical outcomes. Further in vivo studies are essential to validate the long-term efficacy and safety of calcium phosphate bioceramic applications, with an emphasis on patient-specific formulations and rapid prototyping technologies that can personalize treatment for diverse osteomyelitis cases.